A method for rapid sampling and characterization of smokeless powder using sorbent-coated wire mesh and direct analysis in real time - mass spectrometry (DART-MS). Issue 5 (September 2016) - Li, Frederick; Tice, Joseph; Musselman, Brian D.; Hall, Adam B.
Abstract: Improvised explosive devices (IEDs) are often used by terrorists and criminals to create public panic and destruction, necessitating rapid investigative information. However, backlogs in many forensic laboratories resulting in part from time-consuming GC-MS and LC-MS techniques prevent prompt analytical information. Direct analysis in real time - mass spectrometry (DART-MS) is a promising analytical technique that can address this challenge in the forensic science community by permitting rapid trace analysis of energetic materials. Therefore, we have designed a qualitative analytical approach that utilizes novel sorbent-coated wire mesh and dynamic headspace concentration to permit the generation of information rich chemical attribute signatures (CAS) for trace energetic materials in smokeless powder with DART-MS. Sorbent-coated wire mesh improves the overall efficiency of capturing trace energetic materials in comparison to swabbing or vacuuming. Hodgdon Lil' Gun smokeless powder was used to optimize the dynamic headspace parameters. This method was compared to traditional GC-MS methods and validated using the NIST RM 8107 smokeless powder reference standard. Additives and energetic materials, notably nitroglycerin, were rapidly and efficiently captured by the Carbopack X wire mesh, followed by detection and identification using DART-MS. This approach has demonstrated the capability of generating comparable results with significantly reduced analysis time in comparison to GC-MS. All targeted components that can be detected by GC-MS were detected by DART-MS in less than a minute. Furthermore, DART-MS offers the advantage of detecting targeted analytes that are not amenable to GC-MS. The speed and efficiency associated with both the sample collection technique and DART-MS demonstrate an attractive and viable potential alternative to conventional techniques. Highlights: Rapid analytical methods address a critical need in the Forensic Science Community. A rapid analytical approach for the analysis of smokeless powders is proposed. Dynamic headspace and sorbent-coated wire mesh permit rapid sample preparation. Sorbent-coated mesh permits the generation of rich chemical attribute signatures. DART-MS greatly reduces the time required for trace analysis of smokeless powders.